PENGARUH METODE DEMONSTRASI TERHADAP KETERAMPILAN MENGGAMBAR DEKORATIF SISWA SEKOLAH DASAR - Selpy; Nirawati, Resy; Setyowati , Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims: 1) Find out the differences in students' decorative drawing skills between classes that apply the demonstration method and classes that apply the lecture method; 2) Find out how much influence the demonstration method has on elementary school students' decorative drawing skills. This research was carried out at SDN 82 Singkawang. This type of research is quantitative research with a quasi-experimental research method, in the form of a pretest-posttest control group design. The population in this study was all class III students at SDN 82 Singkawang for the 2023/2024 academic year, totaling 50 students, namely 25 class IIIA students and 25 class IIIB students. Samples were taken using purposive sampling technique. The data collection technique uses a test technique in the form of a decorative drawing skills question sheet in essay form containing 5 questions. Data analysis techniques use test Normality, test Homogeneity, test Hypothesis, and test Effect Size. The results of the analysis showed that the data was normally distributed. The results of the research show 1) There are differences in students' decorative drawing skills between classes that apply the demonstration method and classes that apply the lecture method in class III SDN 82 Singkawang. After calculating with the t test two samples obtained - ttabe:> ttrabet count, namely -2.010>-0.858 <2.010 then Ho is rejected and Ha is accepted. 2) The demonstration method has a big influence with a high category on the decorative drawing skills of class III students at SDN 82 Singkawang in the experimental class who received demonstration method treatment with the result of a test effect size of 0.888 with a high category. So it can be concluded that there is an influence of the demonstration method on the decorative drawing skills of class III students at SDN 82 Singkawang.